2006
DOI: 10.3892/or.16.2.225
|View full text |Cite
|
Sign up to set email alerts
|

A cytogenetic analysis in two cases of malignant peripheral nerve sheath tumor showing hypodiploid karyotype

Abstract: Abstract. In this study, we report cytogenetic findings in two cases of malignant peripheral nerve sheath tumor (MPNST) with hypodiploid karyotypes. A G-band technique, multicolor fluorescence in situ hybridization (m-FISH) and comparative genomic hybridization (CGH) were used and compared in this investigation. In both tumors, the G-band and m-FISH analysis demonstrated multiple rearrangements on chromosomes 1-5, 8-12, 15-17, 20 and 21, whereas CGH exhibited gains at 8q and 4q. Both of the structural aberra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 23 publications
(56 reference statements)
0
2
0
1
Order By: Relevance
“…Actualmente, se considera que esta neoplasia maligna, se origina posterior a alteraciones citogenéticas encontradas en los cromosomas 1, 2, 5, 7 -9, 11 -14, 17, 18 y 22, las cuales producen alteraciones en diferentes genes (Woodruff, 1999;Ishiguro et al, 2006;Grobmyer et al, 2008;Perrone et al, 2003), entre los cuales, el más frecuentemente lesionado es la deleción del gen NF1 (Perrone et al;Agesen et al, 2005;Mertens et al, 2000). Las demás alteraciones encontradas son listadas en la Tabla I.…”
Section: Discussionunclassified
“…Actualmente, se considera que esta neoplasia maligna, se origina posterior a alteraciones citogenéticas encontradas en los cromosomas 1, 2, 5, 7 -9, 11 -14, 17, 18 y 22, las cuales producen alteraciones en diferentes genes (Woodruff, 1999;Ishiguro et al, 2006;Grobmyer et al, 2008;Perrone et al, 2003), entre los cuales, el más frecuentemente lesionado es la deleción del gen NF1 (Perrone et al;Agesen et al, 2005;Mertens et al, 2000). Las demás alteraciones encontradas son listadas en la Tabla I.…”
Section: Discussionunclassified
“…The cells and probes were codenatured at 72°C for 2 minutes and subsequently placed in a moist chamber for at least two nights at 37°C. Post-hybridization washing was performed as previously described with minor modifications [ 19 , 20 ]. The slides were air-dried in the dark and counterstained with 4',6-diamidino-2-phenylindole (DAPI II; Abbott Molecular).…”
Section: Methodsmentioning
confidence: 99%
“…116 MPNST also exhibit a wide range of numerical and structural abnormalities involving multiple chromosomes, lacking a common characteristic karyotype. 117,[139][140][141][142][143][144][145][146] CGH studies demonstrated frequent chromosomal imbalances in peripheral nerve sheath tumors, especially losses in chromosome 17, 19p and 22q in NF1-associated neurofibromas, suggesting inactivation of tumor suppressor genes in the development of this type of neurofibroma, whereas in MPNST gains are more frequent than losses, probably relating to protooncogene activation during MPNST progression. 143,144,147,148 To identify genes differentially expressed in MPNST compared with benign tumors, we used cDNA microarray analysis and found that six genes (keratin 18, survivin, tenascin C, adenosine deaminase, collagen type VIa3, and collagen type VIIa1) were significantly upregulated in MPNST, whereas one gene, insulin-like growth factor binding protein 6, was downregulated in MPNST.…”
Section: Sarcomas Displaying Multiple Complex Karyotypic Abnormalitiementioning
confidence: 99%